Respostas

2014-05-21T20:09:52-03:00
Resolva as equacoes usando o artificio da substituicao:

a) x⁶ - 7x³ - 8 =
 0

x
⁶ - 7x³ - 8 = 0   substituindo  x = ∛y

y² - 7x - 8 = 0
a = 1
b = - 7
c = - 8
Δ= b² - 4ac
Δ= (-7)² - 4(1)(-8)
Δ= 49 + 32
Δ = 81

se 
Δ > 0  a função dada tem 2 zeros reais diferentes
então
y = - b - + 
√Δ/2a

y' = - ( -7) - 
√81/2(1)
y' = + 7 - 9/2
y' = - 2/2
y' = - 1

y" = -(-7) + 
√81/2(1)
y" = + 7 + 9/2
y" = 16/2
y" = + 8

então

 
x⁶ - 7x³ - 8 = 0

x = 
∛y

x₁,₂,₃, =  ∛ -1
e
x
₄,₅,₆=  ∛ 8    são 6 raizes

b) (x+1/x)² - 5(x + 1/x) + 6 = 0

        1                            1
(x + -----)²            - 5( x + ----) + 6 = 0
        x                            x

        1          1                5x
(x + -----)(x + -----) - 5x  - -------- + 6 = 0
        x           x                x
         1x     1x     1
( x²  + ----  + ---- + ---) - 5x - 5 + 6 = 0
          x       x     x²

                     1
(x² + 1+ 1 + -------) - 5x + 1 = 0
 
                   x²

               1
x² + 2 + --------- - 5x + 1 = 0
              x²

x
⁴ + 2x² + 1 - 5x³ + x² = 0
----------------------------------------
             x²

x
⁴ -5x³ + 3x² + 1 = 0   substituir y = x²

y² - 5y + 3 + 1 = 0
y² - 5y + 4 = 0
a = 1
b = - 5
c = 4
Δ = b² - 4ac
Δ= (-5)² - 4(1)(4)
Δ= 25 - 16
Δ = 9
se
Δ > 0 então
y = - + √Δ/2a
y' = -(-5) -√9/2(1)
y' = + 5 - 3/2
y' = 2/2
y' = + 1

y" = -(-5) + √9/2(1)
y" = + 5 + 3/3
y" = 8/2
y" = + 4

então
 (x+1/x)² - 5(x + 1/x) + 6 = 0
  x⁴ -5x³ + 3x² + 1 = 0

y = x²

x
²₁   = y     para y = 1
x
²₁ =  1

x
₁ = - + √1

x
₁ = -1
x₁= + 1

x
²₂= y   para y = 4
x²₂ =  4

x₂ = - + √4
x₂ = - 2
x₂ = + 2